Pemungutan Pajak Penghasilan terhadap Jasa Endorsement Konten Kreator Digital - Tiara, Intan; Huzaifah, Zihan; Novikasari, Siti Rahma; Huda, Ni’matul (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
In today’s digital age, endorsement has become one of the main sources of revenue for many digital content creators. Service endorsement is one of the strategies of entrepreneurs to promote their products so that they are known and can enhance marketing. The increasing number of users of this endorsement service make the revenue earned by the digital content creator can be categorized large. However, many digital content creators are unaware of their position in tax law as well as the tax obligations they have. Based on the findings of the tax non-compliance, the researchers looked at two legal issues, namely, first, what is the obligation of the digital content creator to tax the proceeds of endorsement service? Second, how is the tax collection mechanism for endorsement service in Indonesia? This research uses empirical juridical research methods with a conceptual and statutory approach. Primary data was obtained by distributing questionnaires to 8 (eight) digital content creators, and secondary data was obtained by literature study. Analysis of legal material using descriptive-qualitative methods. The result of the study concluded, first, that the digital content creator has met the subjective and objective requirements of income tax so that it is a taxable income and attached to it obligations–in the field of taxation. Secondly, under the digital content creator income tax act, at least 3 (three) norms are imposed, namely the self assessment system method and Article 17 tariff on digital content creator whose income is not deducted from tax by the user of the service, with the method of withholding tax system of Article 23 for the content of digital creator under the umbrella of the agency, and Article 21 tax system when the service user pays and deduces the income tax digital content creator directly.